The Relevance of Interpretation, Argumentation, and Exposition Methods in Contemporary Legal Practice - Ilham Pratama, Muhammad; Wahyu Sururie, Ramdani; Nur Muslimah, Adilla; Yudha Pratama, Brilyan (State of Islamic Institute Langsa, 2025)
Ideally, in legal practice, the application of the methods of interpretation, argumentation, and exposition should create justice and legal certainty. However, in reality, these three methods are often applied inconsistently in various court rulings. This research aims to analyze the relevance of applying the methods of interpretation, argumentation, and exposition in contemporary legal practice in Indonesia. The methodology used is normative legal research with a qualitative approach and phenomenological study, analyzing relevant court decisions. The research findings indicate that although these three methods play an important role in upholding justice, their application remains varied, with some cases showing inconsistencies in the proper use of interpretive methods, resulting in legal uncertainty.